The short-term population health effects of weather and pollution: Implications of climate change - Nicolas R. Ziebarth; Maike Schmitt; Martin Karlsson (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This study comprehensively assesses the immediate effects of extreme weather conditions and high concentrations of ambient air pollution on population health. For Germany and the years 1999 to 2008, we link the universe of all 170 million hospital admissions, along with all 8 million deaths, with weather and pollution data reported at the day-county level. Extreme heat significantly increases hospitalizations and deaths. Extreme cold has a negligible effect on population health. High ambient PM10, O3 and NO2 concentrations are associated with increased hospitalizations and deaths, particularly when ignoring simultaneous weather andpollution conditions. We find strong evidence for harvesting, and that the instantaneous heat-health relationship is only present in the short-term. We calculate that one Hot Day with a temperature higher than 30 C (86 F) triggers adverse health effects valued between 0.07 Euro and 0.52 Euro per resident.
Keywords: I12; I18; Q51; Q53; Q54; Q58; 330; register data; hospital admissions; mortality; weather and pollution; climate change